2021
DOI: 10.1371/journal.pone.0247968
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-induced microstructural changes in shells of laboratory-grown Arctica islandica (Bivalvia)

Abstract: Bivalve shells are increasingly used as archives for high-resolution paleoclimate analyses. However, there is still an urgent need for quantitative temperature proxies that work without knowledge of the water chemistry–as is required for δ18O-based paleothermometry–and can better withstand diagenetic overprint. Recently, microstructural properties have been identified as a potential candidate fulfilling these requirements. So far, only few different microstructure categories (nacreous, prismatic and crossed-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 90 publications
(129 reference statements)
1
16
0
Order By: Relevance
“…In culturing experiments, Höche et al. (2021) also observe shifts in Arctica islandica microstructure in the non‐nacreous hinge plate region of the shell as a function of increasing temperature. Beyond changes in tablet morphology and orientation with temperature, little else has been explored to tie the micron‐ to atomic‐scale mineralogy and crystal structures of nacre aragonite to specific shifts in surrounding environmental and growth conditions, as has been previously examined in coral aragonite (DeCarlo et al., 2017; Farfan et al., 2018).…”
Section: Introductionmentioning
confidence: 95%
“…In culturing experiments, Höche et al. (2021) also observe shifts in Arctica islandica microstructure in the non‐nacreous hinge plate region of the shell as a function of increasing temperature. Beyond changes in tablet morphology and orientation with temperature, little else has been explored to tie the micron‐ to atomic‐scale mineralogy and crystal structures of nacre aragonite to specific shifts in surrounding environmental and growth conditions, as has been previously examined in coral aragonite (DeCarlo et al., 2017; Farfan et al., 2018).…”
Section: Introductionmentioning
confidence: 95%
“…This is typically accomplished by slight etching of the BMUs and/or removal of the intercrystalline organic matrices, e.g., by immersion of the shells in weak acids, bleach or hydrogen peroxide (Crippa et al, 2016). This treatment, however, evokes a violent reaction (Lavkulich and Wiens, 1970), alters the original BMU shape (Höche et al, 2021a) and sometimes affects different materials of the shell heterogeneously. To overcome these problems, an ultrafine chemo-mechanical polishing step was instead employed in this study: shell slabs were polished for 10 minutes on a rotational lap (Buehler MetaServ 2000) at 50 rpm using a Buehler MasterTex polishing cloth and Buehler MasterMet polishing suspension.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…As a previous study revealed a statistically significant relationship between the BMU size in the hinge plate of laboratory grown specimens and temperature (Höche et al, 2021a), the same shell portions were investigated here (953 images; Table 1). For comparison of BMU data in different contemporaneous portions of the shell, the outer shell layer (OSL) of the ventral margin was also studied (241 images; Table 1).…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
See 2 more Smart Citations